Peripartal changes of metabolic and hormonal parameters in Romanian spotted cows and their relation with retained fetal membranes - Rafa, Horatiu; Oroian, Ioan; Cozma, Oana Maria; Morohoschi, Andreea Georgiana; Dumitraș, Daria Antonia; Ștefănuț, Cristina Laura; Neagu, Daniela; Borzan, Alex; Andrei, Sanda (Frontiers in Veterinary Science, 2024)
This clinical study investigates various metabolic and physiological parameters in dairy cows during puerperium. Retained fetal membranes (RFM) is a significant postpartum complication that can affect the overall health, fertility and productivity of dairy cattle. The research focuses on changes in total proteins, albumin, glucose, triglycerides, total cholesterol, aspartate aminotransferase (AST) and alanine aminotransferase (ALT), cortisol, insulin, and insulin-like growth factor 1 (IGF-1) levels among cows experiencing normal post-partum period (NP) and those with RFM. A significant increase in protein levels was noted during the post-partum period in the RFM group, indicating physiological impacts of RFM at this stage. Albumin levels showed significant differences, highlighting a significant biological effect of RFM in the post-partum period. Glucose levels varied significantly in the weeks leading to parturition, suggesting altered metabolic states in cows that suffered RFM. Triglyceride and cholesterol levels were significantly higher during the antepartum period in the group that experienced reproductive failure, indicating substantial alterations in lipid metabolism which could herald the apparition of RFM. AST and ALT levels provided insights into cellular stress and liver function, with significant increases noted around parturition which could be attributed to the substantial physiological strain of parturition itself. Cortisol levels were higher in RFM cows two weeks before parturition, which could indicate an increasing stress response or a physiological preparation for the upcoming labor, and may be more pronounced in cows predisposed to RFM. Insulin levels decreased significantly before and at parturition in RFM cows, indicating a strong energy deficit. IGF-1 levels decreased significantly in RFM cows after parturition. Significant changes in metabolic parameters, such as glucose, triglycerides, and cholesterol levels, delineate the pronounced metabolic challenges faced by cows with RFM. The study elucidates that while some variations are noted as parturition approaches, the most substantial impacts attributable to RFM on metabolic and physiological parameters occur after parturition. These changes may have implications for the health, recovery, and productivity of cows postpartum, suggesting the need for targeted management strategies to mitigate the effects of RFM.